2011
DOI: 10.1586/era.11.19
|View full text |Cite
|
Sign up to set email alerts
|

Improving selection of appropriate urinary diversion following radical cystectomy for bladder cancer

Abstract: Radical cystectomy represents the gold-standard of treatment for invasive bladder cancer. Following cystectomy, various options for urinary diversion may be offered to patients. This article represents an overview of the history of urinary diversion, explains the current selection criteria used at one of the most experienced bladder cancer centers worldwide, and provides an update on the current understanding of continence mechanisms. Furthermore, we review the current literature on quality of life for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…Of the 149 patients included, only nine selected an incontinent diversion [19]. Additionally, absolute and relative contraindications do exist as shown in Table 1, and these should be explained to the patient [20].…”
Section: Patient Selectionmentioning
confidence: 99%
“…Of the 149 patients included, only nine selected an incontinent diversion [19]. Additionally, absolute and relative contraindications do exist as shown in Table 1, and these should be explained to the patient [20].…”
Section: Patient Selectionmentioning
confidence: 99%
“…[1][2][3] While the orthotopic neobladder (ONB) most closely resembles the native bladder, continence outcomes are of particular interest to patients and contribute to the choice of urinary diversion made between physician and patient. 4 However, only a few studies, most of which are more than 10 years old, have prospectively reported continence data on these patients, and none are patient-reported based on validated pictorial questionnaires. [5][6][7][8][9] Various methods have been used in the evaluation of incontinence including voiding diaries, pad tests, urodynamic studies as well as more invasive methods.…”
Section: Introductionmentioning
confidence: 99%
“…Continence, metabolic disturbances, body image and psychological aspects affect QoL in both men and women [9,10,11]. In addition to this, depending on age, men are often concerned with sexual function.…”
Section: Introductionmentioning
confidence: 99%